Modification of silica-supported tungsten neosilyl oxo precatalysts: impact of substituted phenol on activity and stability in olefin metathesis. Issue 24 (18th November 2016) - Bouhoute, Y.; Del Rosal, I.; Szeto, K. C.; Merle, N.; Grekov, D.; De Mallmann, A.; Le Roux, E.; Delevoye, L.; Gauvin, R. M.; Maron, L.; Taoufik, M.
Abstract : Development of a novel and convenient strategy to access a large variety of highly active tungsten oxo olefin metathesis pre-catalysts. Abstract : A novel strategy to access a large variety of tungsten oxo pre-catalysts for olefin metathesis involving post-treatment of [(SiO)W(O)(CH2 SiMe3 )3 ], 1b, with the desired spectator ligands is presented. This method allowed establishing structure–reactivity relationships in propylene metathesis as a function of the spectator ligands of tungsten oxo species. Thus, the novel pre-catalysts [(SiO)W(O)R2 X], 2a–c (X = 2, 6-dimethylphenoxide, 2-trifluoromethylphenoxide, pentafluorophenoxide), are obtained by modification of well-defined monopodal species1b by substituted phenols along with TMS release. These were demonstrated by mass balance analysis, elemental analysis, IR, advanced solid-state NMR (1D and 2D 1 H, 13 C and 19 F) and EXAFS. The modified materials were proved to lead to stable and efficient supported tungsten oxo catalysts for propene metathesis under dynamic conditions at 80 °C.